Scientific communication: the appropriation that rural extension workers make of the new vehicles of communication through of the web (Research, Society and Development, 2020)
Since its introduction in Brazil, in the 1990s, the web has aroused interest as a means of communication, information and interaction between people, institutions and professionals from different areas, including rural extension and agricultural research. This study sought to analyze the appropriation that extensionists make of the new communication vehicles through of the web, comparing their incorporation with conventional channels. The research used the survey method to collect data. It is concluded that the web as a means of communication and interaction is not yet appropriated by rural extension workers.